Investigating optimal technique in the presence of motor system noise: application to the double layout somersault dismount on high bar - Hiley, M. J.; Yeadon, M. R. (Journal of Sports Sciences, 2016)
Minimising joint torque is often used as an optimisation criterion when investigating human movement. Alternatively, an aspect of performance may be chosen to be maximised when investigating sporting movements. The aim of the study was to optimise the technique in the backward giant circle prior to a double layout somersault dismount from the high bar using various criteria to determine which best characterised the technique adopted by a gymnast. Ten recorded gymnast trials were used to determine bar release parameters and the level of noise in the gymnast`s movements. A computer simulation model of a gymnast and bar was used to optimise giant circle technique under three criteria: minimising joint torques, maximising the release window and maximising success in the presence of motor system noise. Local and global optimisations of technique were performed using the three criteria starting from the average technique of the 10 recorded trials. All global optimum solutions diverged from the gymnast`s technique. The local optimum for maximising success in the presence of noise had a success rate comparable with the global optimum (98% vs. 100%, respectively). It is concluded that the gymnast`s technique is characterised by maximising success despite operating with motor system noise.